IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MEMBENTUK BUDAYA ISLAMI - Yusuf, Al Haris Muhammad; Faridi, Faridi; Mardiana, Dina (Tarbiyatuna Kajian Pendidikan Islam, 2024)
This research discusses the implementation of character education in establishing Islamic culture in the Taman Pendidikan Al-Qur’an (TPQ) Nurut Taubah, Dieng Village, Gondanglegi District. This research aims to describe the character values in establishing the Islamic culture of students at TPQ Nurut Taubah. The researcher used a qualitative research method, case study type. Data collection techniques that are used observation, interviews and documentation. The results of the research state that the implementation of character education in establishing Islamic culture at TPQ Nurut Taubah has been carried out well, TPQ Nurut Taubah provides shorter teaching hours accompanied by collaboration with parents, providing resources, guidance, and effective communication with parents to support the students learning at home. TPQ provides strong Islamic religious education to students, including an understanding of the teachings of the Qur’an, and emphasizes the importance of ukhuwah, despite several obstacles during the Covid-19 pandemic. These obstacles include: 1) Limited access to learning materials. 2) Loss of student participation. 3) Influence of friends. In order to overcome these obstacles, TPQ Nurut Taubah took solutive steps which are: 1) Maximizing the use of existing resources and grouping students to read the Iqra' book. 2) Holding lessons of general subjects from 18.00 until before Isha'. 3) TPQ maintains communication with students' parents.